Fuzzy logic decission maker for automatic feeder and water quality monitoring system - Vivien Arief Wardhany; Herman Yuliandoko; Subono Subono; A Wildan J; Tomy Iskandar; M. Udin Harun A. L; I Gede Puja A (Institute of Advanced Engineering and Science, 2021)
Feeding is one of the most important factors in vanammei shrimp culture. Feeding time must be scheduled regulary and it is prohibit from being late. Because it can affect to the development and growth of vanammei shrimp. The Research of monitoring and control system of vanammei shrimp feeding continues to be developed. The development of hardware and software in this study prioritizes monitoring of pH conditions, oxygen levels, and pond temperatures. The measurement results of pH, oxygen levels and pond temperature can be used as decision makers for vanammei shrimp feeding schedules. The decision making system using the Fuzzy Logic method. The development of control devices for feeding aims to set a schedule for feeding automatically. The use of monitoring devices and automatic Feeder control of shrimp feeding can reduce the accumulation of leftover shrimp feed, so that feeding can be more efficient.